Taxonomic, phylogenetic, and trait Beta diversity in South American hummingbirds (2014)
ABSTRACT: Comparison of the taxonomic, phylogenetic, and traitdimensions of beta diversity may uncover the mechanisms that gen-erate and maintain biodiversity, such as geographic isolation, envi-ronmental filtering, and convergent adaptation. We developed anapproach to predict the relationship between environmental and geo-graphic distance and the dimensions of beta diversity. We tested thesepredictions using hummingbird assemblages in the northern Andes.We expected taxonomic beta diversity to result from recent geo-graphic barriers limiting dispersal, and we found that cost distance,which includes barriers, was a better predictor than Euclidean dis-tance. We expected phylogenetic beta diversity to result from his-torical connectivity and found that differences in elevation were thebest predictors of phylogenetic beta diversity. We expected high traitbeta diversity to result from local adaptation to differing environ-ments and found that differences in elevation were correlated withtrait beta diversity. When combining beta diversity dimensions, weobserve that high beta diversity in all dimensions results from adap-tion to different environments between isolated assemblages. Com-parisons with high taxonomic, low phylogenetic, and low trait betadiversity occurred among lowland assemblages separated by the An-des, suggesting that geographic barriers have recently isolated lineagesin similar environments. We provide insight into mechanisms gov-erning hummingbird biodiversity patterns and provide a frameworkthat is broadly applicable to other taxonomic groups.